CAPAIAN KEMAMPUAN PENALARAN STATISTIS MAHASISWA BERBASIS EXPERIENTAL LEARNING - Frena Fardillah; Aan Subhan Pamungkas (JPPM (Jurnal Penelitian dan Pembelajaran Matematika), 2018)
This study aims to determine the improvement of statistical reasoning ability of students who take the course of industry-based statistics eksperiential learning. This study is a quasi-experimental study, in which there are two classes. One class as an experimental class that accepts experiential learning learning and a control class as a comparative class. The population of this study is industrial engineering students, with samples of industrial engineering students who contract industrial statistics courses. By using lecture syntax consisting of stages of concrete experience, reflective observation, abstract conceptualization and active experimentation. At the beginning and end of the study students are given a statistical skills reasoning test. The data obtained were analyzed quantitatively. The result of the study that the class that received experimental learning learning is good for the students of statistics. Keywords: Statistical Reasoning, Experiential Learning